ANALYSIS OF ENGLISH PROFICIENCY LEVEL OF SMKN 3 JAKARTA STUDENTS BASED ON THE RESULTS OF THE TOEIC PREDICTION TEST - Redjeki Agoestyowati1; Umi Hani Makmuroh (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
English proficiency is one of the essential competencies required to compete in the global workforce. One of the most widely used instruments for measuring workplace English communication skills is the Test of English for International Communication (TOEIC). This study aims to analyze the English proficiency levels of students at SMKN 3 Jakarta based on their TOEIC Prediction Test results conducted on May 26, 2026. The study employed a descriptive quantitative approach involving 209 students as participants. Data were collected from TOEIC Prediction Test scores and analyzed using descriptive statistics, including mean, median, standard deviation, frequency, and percentage. The results revealed that students' TOEIC scores ranged from 145 to 905, with a mean score of 560.53 and a median of 580. Most students were classified in the Intermediate category (64.6%), followed by Elementary (19.6%), Basic Working Proficiency (12.0%), Novice (3.3%), and Advanced (0.5%). These findings indicate that the majority of students possess intermediate English proficiency, enabling them to understand general communication and some workplace-related communication. The findings may serve as a basis for schools in designing more effective English language development programs.